Improved compatibility of PET/HDPE blend by using GMA grafted thermoplastic elastomer. Issue 17 (21st November 2020) - Pan, Yang; Wu, Guangfeng; Ma, Huifang; Zhou, Shujie; Zhang, Huixuan
ABSTRACT: Herein, graft-modified ethylene-1-octene copolymer (POE- g -GMA) and styrene-butadiene-styrene triblock copolymer (SBS- g -GMA) were found to be excellent reactive compatibilizers for immiscible poly(ethylene terephthalate) (PET)/high-density polyethylene (HDPE) blends via in-situ reaction compatibilization. With increase in compatibilizer amount, uniform phase morphology was observed in all the blends. Thus, exhibiting enhanced mechanical properties, especially, the notched Izod impact strength. In comparison with SBS- g -GMA, compatibilizer POE- g -GMA demonstrated greater impact on the compatibility. The addition of 15% POE- g -GMA produced blends with best mechanical properties. Besides, both POE- g -GMA and SBS- g -GMA enhanced the melt viscosity of PET/HDPE blends. Graphical Abstract: